Lay Catholic Support for Exiled Polish Intellectuals in Britain, 1942–1962. Issue 4 (October 2017) - Bush, Jonathan
This article examines the hitherto unexplored role of lay Catholics in the tertiary education of Polish exiles in Britain, from the early 1940s to the beginning of the Second Vatican Council in 1962. It will examine the work of the Newman Association, a predominantly lay Catholic graduate society, as a case study to reveal how lay activism towards European exiles was influenced by a range of social, theological and political factors. It will highlight the ways in which support for Polish Catholic education could be manifested, including the establishment of a cultural hub in London, a scholarship programme to assist Polish students in British and Irish universities, and the development of cultural links with individuals and organisations within Poland. Ultimately, this article demonstrates the growing confidence of educated lay Catholics in breaking out of their historically subordinate role within the English Catholic Church in the years prior to Vatican II.